Shear strength characteristics of fibrous peat soil [compact disc] - 329740 Ushaa Nair Pannir Selvam (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006